A MULTICULTURAL-BASED MODEL FOR THE DEVELOPMENT OF ISLAMIC EDUCATION CURRICULUM TO PROMOTE RELIGIOUS MODERATION: A CASE STUDY AT PADAMARA STATE HIGH SCHOOL 1 - Zen Magata Larashati; Fika Umul Mulyanti; Rizqi Agus Kurniawan (Jurnal Konseling Pendidikan Islam, 2026)
This research aims to analyze and conceptualize a multicultural-based Islamic Education (PAI) curriculum development model in strengthening religious moderation within pluralistic school settings. This research employs a qualitative approach with a case study design conducted at SMA Negeri 1 Padamara, Purbalingga, which represents a religiously diverse student population. Data were collected through in-depth interviews, participant observation, and document analysis involving school principals, teachers, and students. Data analysis was carried out through data reduction, coding, thematic categorization, and source triangulation to ensure validity. The findings reveal that the strengthening of religious moderation is not limited to formal instruction but is implemented through an integrative model consisting of three main dimensions: intracurricular, co-curricular, and school culture. These dimensions interact to create a holistic learning experience that fosters tolerance, balance, and respect for diversity. However, the implementation also faces challenges, including varying levels of teacher understanding of religious moderation and uneven student engagement. This study contributes by proposing a contextual and applicable conceptual model of multicultural-based Islamic education curriculum development in pluralistic school environments. The findings highlight the importance of a whole-school approach in fostering sustainable religious moderation.